Romani Communities and Transformative Change A New Social Europe - Ryder, Andrew; Taba, Marius; Trehan, Nidhi (Policy Press, 2020)
"Available Open Access under CC-BY-NC licence. The turn towards a Social Investment approach to welfare implies deploying resources to enhance human capital and mobilise the productive potential of citizens, starting in early childhood.Available Open Access under CC-BY-NC-ND. Drawing on Roma community voices and expert research, this book provides a powerful tool to challenge conventional discourses and analyses on Romani identity, poverty and exclusion. Through the transformative vehicle of a 'Social Europe', this edited collection presents new concepts and strategies for framing social justice for Romani communities across Europe. The vast majority of Roma experience high levels of exclusion from the labour market and from social networks in society. This book maps out how the implementation of a new 'Social Europe' can offer innovative solutions to these intransigent dilemmas. This insightful and accessible text is vital reading for the policymaker, practitioner, academic and activist. This edited collection brings regional and local realities to the forefront of social investment debates by showcasing successes, challenges and setbacks of Social Investment policies and services from ten European countries: Italy, UK, Sweden, Finland, Greece, Germany, Poland, the Netherlands, Hungary, and Spain. It provides practical, accessible illustrations of good practice, routes to success, and lessons learned. The book is informed throughout by engagement with service users and local communities, and features many previously unheard voices including front-line workers, local decision makers, volunteers and beneficiaries."